Grace Pailthorpe et Reuben Mednikoff à Vancouver. La transmission du surréalisme au Canada anglais, 1942–1946 - Larocque, Yves (RACAR : Revue d'art canadienne / Canadian Art Review, 2007)
In July 1940, the British Surrealist artists Dr Grace W. Pailthorpe (also a prominent psychiatrist) and Reuben Mednikoff set sail for the United States. After a two-year stay in New York City and Berkeley in California, they moved in July 1942 to British Colombia, Canada, where Dr Pailthorpe accepted a position at the Provincial Mental Institute of Essondale. Later in Vancouver, she founded the Association for the Scientific Treatment of Delinquency and was invited with her husband by the Vancouver Art Gallery to exhibit their paintings and give a conference on Surrealism. This series of events made British Colombia the launching pad for Surrealism in Western Canada with one Surrealist exhibition and three conferences on Surrealism. One of these talks was even broadcast by the Canadian Broadcasting Corporation during the radio show Mirror for Women. Vancouver warmly welcomed Breton's movement in contrast to Toronto, which held a Surrealist exhibition at the 1938 Central National Exhibition. The reasons for Vancouver’s openness are twofold: most importantly, Pailthorpe’s association with science lent credibility; and Vancouver at the time was open to new ideas. This article focuses on the Canadian sojourn of these two important artists in the context of Canada’s adoption of Surrealist ideas (Automatism being the most important) and the publication of the CBC transcripts of Dr Pailthorpe’s seminar.